Simvastatin Increases the Ability of Roflumilast N-oxide to Inhibit Cigarette Smoke-Induced Epithelial to Mesenchymal Transition in Well-differentiated Human Bronchial Epithelial Cells in vitro. (4th May 2015) - Milara, Javier; Peiró, Teresa; Serrano, Adela; Artigues, Enrique; Aparicio, Jesus; Tenor, Herman; Sanz, Celia; Cortijo, Julio
Abstract: Background: Cigarette smoking contributes to epithelial-mesenchymal transition (EMT) in COPD small bronchi as part of the lung remodeling process. We recently observed that roflumilast N-oxide (RNO), the active metabolite of the PDE4 inhibitor roflumilast, prevents cigarette smoke-induced EMT in differentiated human bronchial epithelial cells. Further, statins were shown to protect renal and alveolar epithelial cells from EMT. Objectives: To analyze how RNO and simvastatin (SIM) interact on CSE-induced EMT in well-differentiated human bronchial epithelial cells (WD-HBEC) from small bronchi in vitro . Methods: WD-HBEC were stimulated with CSE (2.5%). The mesenchymal markers vimentin, collagen type I and α-SMA, the epithelial markers E-cadherin and ZO-1, as well as β-catenin were quantified by real time quantitative PCR or Western blotting. Intracellular reactive oxygen species (ROS) were measured using the H2 DCF-DA probe. GTP-Rac1 and pAkt were evaluated by Western blotting. Results : The combination of RNO at 2 nM and SIM at 100 nM was (over) additive to reverse CSE-induced EMT. CSE-induced EMT was partially mediated by the generation of ROS and the activation of the PI3K/Akt/β-catenin pathway. Both RNO at 2 nM and SIM at 100 nM partially abrogated this pathway, and its combination almost abolished ROS/ PI3K/Akt/β-catenin signaling and therefore EMT. Conclusions: The PDE4 inhibitor roflumilast N-oxide acts (over)additively with simvastatin to prevent CSE-induced EMT in WD-HBEC in vitro .